Video Analytics оf Aerial Objects - Tevyashev, A. D.; Shostko, I. S.; Zemlyaniy, O. (Друкарня Мадрид, 2020)
This work is devoted to the problem of creating and using video analytics of aerial objects with the aim to solve the variety of problems of airspace monitoring in the visible and infrared frequency ranges for security systems of general and special purpose.
Keywords: aerial object; video analytics; monitoring; security systems